Answer:
[tex]AB = 6[/tex] [tex]BC = 8[/tex] [tex]AC = 10[/tex]
Step-by-step explanation:
The picture of the triangle is missing.
Given
[tex]AC = x + 4[/tex]
[tex]BC = x + 2[/tex]
[tex]AB = x[/tex]
Required
Find x
When Pythagoras theorem is applied, we have:
[tex](AC)^2 = (BC)^2 + (AB)^2[/tex]
This is so, because AC is the hypotenuse
So, we have:
[tex](x+4)^2 = (x+2)^2 + x^2[/tex]
Open brackets
[tex]x^2 + 4x + 4x + 16 = x^2+2x + 2x + 4 + x^2[/tex]
[tex]x^2 + 8x + 16 = x^2+4x + 4 + x^2[/tex]
Collect Like Terms
[tex]x^2 -x^2 - x^2 + 8x -4x + 16 - 4 = 0[/tex]
[tex]- x^2 + 4x + 12 = 0[/tex]
Expand:
[tex]- x^2 + 6x -2x+ 12 = 0[/tex]
Factorize:
[tex]-x(x -6) -2(x- 6) = 0[/tex]
[tex](-x -2)(x- 6) = 0[/tex]
Split
[tex]-x - 2 = 0[/tex] or [tex]x - 6 = 0[/tex]
[tex]-x = 2[/tex] or [tex]x = 6[/tex]
[tex]x =-2[/tex] or [tex]x = 6[/tex]
Because [tex]BC = x + 2[/tex] and [tex]AB = x[/tex]
[tex]x =-2[/tex] can not be considered.
Hence:
[tex]x = 6[/tex]
Substitute 6 for x in
[tex]AC = x + 4[/tex]
[tex]BC = x + 2[/tex]
[tex]AB = x[/tex]
[tex]AC = 6 + 4[/tex]
[tex]AC = 10[/tex]
[tex]BC = 6 + 2[/tex]
[tex]BC = 8[/tex]
[tex]AB = 6[/tex]